Knee-ankle-foot orthoses for treating posterior knee pain resulting from genu recurvatum: Efficiency, patients' tolerance and satisfaction - Benoit Requier; Laurent Bensoussan; Julien Mancini; Alain Delarque; Jean Michel Viton; Marjorie Kerzoncuf (Medical Journals Sweden, 2018)
Objective: To assess the efficiency of knee-ankle-foot orthoses for treating painful genu recurvatum, and to determine users' tolerance and satisfaction. Patients: Patients included in the study had a genu recurvatum during the stance phase, confirmed by a medical doctor on physical examination. A total of 27 patients with 31 knee-ankle-foot orthoses were included. Methods: The main outcome was scored on a verbal numerical rating scale (VNRS) before and at least 3 months after a knee-ankle-foot orthosis was fitted, and scored on a verbal numerical pain rating scale (VRS). Secondary outcomes were rated with the Quebec User Evaluation of Satisfaction with assistive Technology (QUEST). Results: After fitting the knee-ankle-foot orthosis, the median VNRS pain score decreased from 85/100 to 25/100 (p ≤ 0.001) and the description of pain on the VRS decreased from "extreme" to "mild" (p ≤ 0.001). The QUEST total score was 4.0. Conclusion: Treating a painful genu recurvatum with a knee-ankle-foot orthosis reduced the pain efficiently whatever the patients' diagnosis, and high scores were obtained for patients' satisfaction.